2012
DOI: 10.1002/ejsp.1840
|View full text |Cite
|
Sign up to set email alerts
|

On the relevance of morality in social psychology: An introduction to a virtual special issue

Abstract: Recently, social psychology has become central in the study of morality. This turn to morality as a topic builds on social psychologists' long‐standing interest in issues closely related to morality, such as cooperation, empathy, fairness, social norms and deviance. The present paper introduces a (virtual) special issue on morality by highlighting some of the 41 articles on “moral” or “morality” that have appeared in the European Journal of Social Psychology from 1973 to the present. The nineteen highlighted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…However, this distinction has recently been refined when it was shown that the warmth dimension encompasses both perceptions of sociability and morality (Leach, Ellemers, & Barreto, ). Further, several studies have shown that perceptions of morality, rather than sociability or competence, have primacy in evaluating others (e.g., Pagliaro, ) and in forming perceptions about out‐groups (e.g., Brambilla, Sacchi, Rusconi, Cherubini, & Yzerbyt, ). For instance, research has revealed that moral traits are dominant in face‐perception, being chronically accessible and playing a key role in interpersonal impression formation (Goodwin, Piazza, & Rozin, ; Todorov, Olivola, Dotsch, & Mende‐Siedlecki, ).…”
Section: Relational and Emotional Obstacles To Reconciliationmentioning
confidence: 99%
“…However, this distinction has recently been refined when it was shown that the warmth dimension encompasses both perceptions of sociability and morality (Leach, Ellemers, & Barreto, ). Further, several studies have shown that perceptions of morality, rather than sociability or competence, have primacy in evaluating others (e.g., Pagliaro, ) and in forming perceptions about out‐groups (e.g., Brambilla, Sacchi, Rusconi, Cherubini, & Yzerbyt, ). For instance, research has revealed that moral traits are dominant in face‐perception, being chronically accessible and playing a key role in interpersonal impression formation (Goodwin, Piazza, & Rozin, ; Todorov, Olivola, Dotsch, & Mende‐Siedlecki, ).…”
Section: Relational and Emotional Obstacles To Reconciliationmentioning
confidence: 99%
“…However, recent research has revealed that moral judgments – rather than competence judgments – are central in the impressions people form of other individuals and groups (Brambilla and Leach, in press; Goodwin, Piazza and Rozin, ). Evaluations of other people's morality (rather than their competence) also dominate behavioural responses towards them, such as the willingness to approach and help rather than avoiding and ignoring them (for overviews, see Brambilla and Leach, in press; Pagliaro, ). Accordingly, in contexts where morality (e.g.…”
Section: Social Identity and Organizational Moralitymentioning
confidence: 99%
“…One dimension that appears to be important in such ingroup and outgroup evaluations is morality. By now, several studies have shown that perceptions of morality, rather than sociability or competence have primacy in evaluating others (e.g., Pagliaro, 2012) and in forming perceptions about outgroups (e.g., Brambilla, Sacchi, Pagliaro, & Ellemers, 2013). For instance, research has revealed that moral traits are dominant in face-perception playing a key role in interpersonal impression formation (Goodwin, Piazza, & Rozin, 2014).…”
Section: Morality and Group Perceptionsmentioning
confidence: 99%